The world gives way eaudiobook A novel. - Levien, Marissa (2021)
A Ray Bradbury Prize for Science Fiction, Fantasy & Speculative Fiction Finalist In a near-future world on the brink of collapse, a young woman born into servitude must seize her own freedom in this glittering debut with a brilliant twist—perfect for fans of Station Eleven , Karen Thompson Walker, and Naomi Alderman. In fifty years, Myrra will be free. Until then, she's a contract worker. Ever since she was five, her life and labor have belonged to the highest bidder on her contract—butchers, laundries, and now the powerful, secretive Carlyles. But when one night finds the Carlyles dead, Myrra is suddenly free a lot sooner than she anticipated—and at a cost she never could have imagined. Burdened with the Carlyles' orphaned daughter and the terrible secret they died to escape, she runs. With time running out, Myrra must come face to face with the truth about her world—and embrace what's left before it's too late. A sweeping novel with a darkly glimmering heart, The World Gives Way is an unforgettable portrait of a world in freefall, and the fierce drive to live even at the end of it all. A New York Times Best Sci-Fi and Fantasy Novel of 2021 A Fortune Magazine Best Book of 2021 "A staggering marvel."— The New York Times " The World Gives Way has a sweeping world rich in lore and an electric plot."—Brandon Taylor, Booker Prize-nominated author of Real Life